NILAI EDUKASI ETNOHISTORIS MASJID URBAN: MEMBINGKAI PERADABAN DARI RITUS JUMATAN DI PUSAT PERBELANJAAN“CITY OF TOMORROW” SURABAYA - Muhammad Thohir; Lailatul ULa; Widatul Lutfiyah (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2021)
The majority of Muslim workers in industrial areas are not only required to be able to work quickly in meeting targets, but also face obligations as servants of God, namely praying fardhu. Meanwhile, for Friday prayers, most of the factory workers are travelers whose muqim limits are fulfilling the requirements for Friday prayers in the realm of khilafiyah. The study aims to reveal how the existence of mosques in shopping centers that are used for Friday prayers within the industrial community. Through a phenomenological qualitative approach based on field research, the research was carried out using ethnohistorical methods, namely research activities to understand people's ways. interact by working together through phenomena in the daily life of social and cultural groups. The object of research is the industrial mosque in the CITOMall Surabaya area. The sampling was snowballing and purposive. Data were collected through interviews and observations. After that, the analysis was carried out using inductive deductive techniques.The results showed that in the context of culture, it is illustrated how the social behavior of the urban industrial community in looking for God, one of which is through the Friday rite. The end, this study offers knowledge about the educational values of the ethonohitorical phenomenon of urban mosques